Structural and chemical modifications of porous silicon for biomedical applications - Mäkilä, Ermei (fi=Turun yliopisto|en=University of Turku|, 2024)
The versatility in properties of porous silicon (PSi) has enabled a broad spectrum of applications, ranging from microelectronics and various types of sensors to its use as a biocompatible material in drug delivery. Structural properties of PSi were shown in this work to be adaptable post-fabrication using thermal annealing. Control over the average pore size of the material proved to be beneficial, when adjustments were necessary to accommodate larger biomolecules within the pores of the PSi. Furthermore, a facile method of fabricating PSi nanoparticles was introduced using a multilayer approach with a stepwise electrochemical etching process, where the comminution of the material was guided with formation of fragile, high porosity perforation layers at specific intervals. This method has been proven successful, being utilized in over 70 publications so far. For extended control over biocompatibility and biodistribution of PSi micro- and nanoparticles, two new surface modifications based on hydrolytically stabilized PSi were introduced. Amine-terminated thermally carbonized PSi, capable of carbodiimide crosslinking for further functionalization with biomolecules, and an alkyne-terminated hydrocarbonized PSi, enabling the use of click chemistry -based addition reaction for secondary functionalization. Solid-state properties of confined drug molecules adsorbed into PSi microparticles were also studied. As PSi is known to enhance aqueous dissolution and cellular permeability of poorly soluble drugs, more accurate information was sought on the effects of the mesoscale confinement. Small molecule drugs were observed to partially have a liquid-like behavior according to solid-state NMR analysis and participate in interactions with the pore walls, according the availability of specific functional groups. Slight disruption in short-range order of the adsorbed drugs was also found, as the confinement appeared to reduce the true density of the drug molecules below that of a bulk amorphous state. Study over the conditions for efficient drug adsorption into the pores showed the importance of solvent and drug solution concentration selection. Optimal choices enabled high drug payload within the PSi, without precipitation of crystalline drug on the external surface of the PSi microparticles.

Huokoisen piin (porous silicon, PSi) monipuoliset ominaisuudet ovat mahdollistaneet runsaasti erilaisia sovelluksia, lähtien mikroelektroniikasta ja ilmaisimista aina tämän käyttöön bioyhteensopivana materiaalina lääkeannostelussa. Tässä työssä osoitettiin huokoisen piin rakenteen olevan jälkikäteen muokattavissa hallitusti lämpökäsittelyn avulla. Huokoskokoa kasvattamalla mahdollistettiin tarpeen vaatiessa suurempien biomolekyylien pääsy huokosiin. Tämän lisäksi esiteltiin menetelmä huokoisen piin nanopartikkelien valmistamiseksi syövyttämällä sähkökemiallisesti huokoinen monikerrosrakenne, missä tasaisin välimatkoin sijaitsevat hauraat korkean huokoisuuden kerrokset toimivat murtumista edistävinä kohtina. Menetelmää on sittemmin hyödynnetty tähän mennessä yli 70:ssä tieteellisessä julkaisussa. Huokoisen piin mikro- ja nanopartikkelien bioyhteensopivuuden ja kulkeutumisen hallintaan työssä kehitettiin kaksi uutta pintakemiallista muunnosta huokoiselle piille, mikä oli esikäsitelty heikosti veteen liukenevaksi. Muunnokset perustuivat vapaiden amiiniryhmien ja alkyynien saatavuuteen huokoisen piin pinnoilla. Näistä edellinen mahdollisti biologisen funktionalisoinnin karbodi-imidisilloituksen kautta, jälkimmäisen puolestaan mahdollistaen monipuolinen funktionalisointi kupariavusteisen sykloadditioreaktion kautta. Lääkemolekyylien fysikaalista olotilaa nanokokoluokan huokosissa tutkittiin huokoisen piin mikropartikkelien avulla. Huokosiin adsorboitujen niukkaliukoisten lääkeaineiden tiedetään liukenevan tehokkaasti veteen, mutta syitä tälle voi olla useita. Pienmolekyylilääkkeiden havaittiin olevan osittain nestemäisessä muodossa huokosten sisällä NMR-tutkimusten mukaan. Molekyylien lähijärjestys vaikutti myös osittain muuttuneen, huokosiin adsorboituneen lääkeaineen tiheyden ollessa tavallista amorfista tilaa alhaisempi. Lääkeaineen adsorptiota huokosiin pyrittiin myös tehostamaan seuraamalla liuottimen ja lääkeaineliuoksen konsentraation vaikutusta. Sopivin parametrein saavutettiin korkea lääkkeen hyötykuorma, ilman lääkemolekyylien kiteytymistä huokoisen piin mikropartikkelien ulkopinnoille.
Keywords: porous silicon; surface chemistry; nanoparticles; microparticles; confinement; drug delivery; lääkkeet; annostelu; huokoinen pii; pintakemia; nanopartikkelit; mikropartikkelit